APLIKASI PENDETEKSI PLAGIARISME TUGAS DAN MAKALAH PADA SEKOLAH MENGGUNAKAN ALGORITMA RABIN KARP - Danny Steveson; Halim Agung; Fendra Mulia (Jurnal Algoritma, Logika dan Komputasi, 2018)
Plagiarism is a very frequent problem in all aspects of one occurring in school. There is often plagiarism on the content of the papers or assignments collected by the students. This is to support the decreasing creativity of students in giving ideas and personal opinions on the task given. To answer the above problems then this research using Rabin-Karp algorithm. Rabin-Karp algorithm is a string search algorithm that uses hashing to find one of a series of string patterns in text. Using this application, the user can compare document 1 with another document, which gives results in sentence similarity, then spelled out per word, followed by per hashing and is calculated from the average number of percentages. The test in this research is done by taking samples 50 times and in comparison between percentage with Rabin Karp algorithm and percentage with manual taking. Testing is done by comparing one document with another document. Based on the result of the research, it can be concluded by using Rabin Karp Algorithm, which can be implemented in plagiarism application evidenced by the test using 50 test samples with 43 samples of success of 14.22%.Keywords: document , Rabin Karp Algorithm, Dice Sorensen Index, Plagiarism, sentence, word